The autobiography of Malcolm X with the assistance of Alex Haley - Haley, Alex. (London Penguin Books, 2007)
Malcolm X is one of the twentieth century's most controversial figures. Celebrated and vilified the world over for his courageous but bitter fight to gain for millions of black men and women the equality and respect denied them by their white neighbours, he inspired as many people in the United States as he caused to fear him.
Includes index
Keywords: X, Malcolm 1925-1965.